Composite membrane based on covalent organic framework as well as preparation method and application of composite membrane
Through the use of the technology of co -price organic framework composite film in the lithium -magnesium separation film, the problem of high cost and low efficiency in the process of lithium -magnesium separation in the existing technology has been solved, and high -efficiency and low -cost lithium ion separation and recycling.
Patent Information
- Application Number
- CN202411443261.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems such as high cost, long time, low efficiency, high pollution, corrosive equipment and unfavorable for sustainable development in the extraction of lithium ore resources, especially in the process of separation of lithium-magnesium in salt lake brine.
The composite film based on covalent -based organic framework is used to combine 3D COF membrane and polypropylene flexible base through the interface polymerization to form an ion separation film with excellent selectivity and permeability.
It achieves efficient separation and recovery of lithium ions in salt lake brine, reduces costs, improves efficiency, and has good mechanical properties and stability, making it suitable for industrial applications.
Smart Images

Figure CN119345916A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of preparation of covalent organic framework composite membranes for ion separation membranes, and in particular to a composite membrane based on a covalent organic framework and a preparation method and application thereof. Background Art
[0002] Lithium ore resources are key resources for global decarbonization, and the number of new energy vehicles continues to increase. The growth rate of new energy vehicles continues to grow. New energy vehicles are mainly based on lithium batteries, which leads to a continuous increase in the demand for raw material lithium ore. There are three main forms of lithium ore resources: salt lake brine lithium ore in closed basins, pegmatite-type hard rock lithium ore, and sedimentary rock-type clay lithium ore. Among them, salt lake brine lithium ore accounts for 62.6% of the total global lithium ore resources. At present, the extraction method of salt lake lithium ore in industry is mainly based on traditional methods such as precipitation and extraction. The disadvantages of traditional methods are very obvious, with high cost, long time, low efficiency, high pollution, corrosion of equipment, and impact on production, which is not conducive to sustainable development. The use of new membrane separation technology is imminent. The three-dimensional new covalent organic framework material (3D COF) can work stably for a long time in salt lakes with high magnesium-lithium ratios.
[0003] The global demand for lithium has greatly increased due to the widespread use of lithium batteries. Lithium mineral resources are mainly concentrated in salt lakes. Most salt lakes have a high magnesium-to-lithium ratio, but the physical and chemical properties of lithium and magnesium are very similar, so it is particularly necessary to develop an efficient lithium-magnesium separation method. Compared with traditional separation methods, membrane separation technology only relies on concentration, pressure, electric field, etc. to achieve separation, and does not involve chemical, biological and thermal reactions. Membrane separation technology has the advantages of high separation efficiency and stable lithium separation, and is an ideal method for extracting lithium from salt lake brine. At present, a variety of membrane materials for lithium-magnesium separation have been reported, including polymer nanofiltration membranes, heavy ion irradiation membranes, microporous polymer membranes, clay membranes, GO membranes, MOF membranes, POC membranes, COF membranes, etc. Among them, COF membranes have the characteristics of low density, large surface area, adjustable pore size, and easy-to-customize functionality. Appropriate pore size and functional sites are conducive to high selectivity in the lithium-magnesium separation process; the ordered pore structure can make it have a high permeation flux; in addition, the high stability and permanent pores of COF membranes guarantee its potential for application in practical applications. Summary of the invention
[0004] Technical problems to be solved: In order to solve the technical problems existing in the prior art such as high cost, long time, low efficiency, high pollution, equipment corrosion, impact on production, and being unfavorable to sustainable development, a composite membrane based on a covalent organic framework and its preparation method and application are provided. The composite membrane can separate lithium ions and divalent transition metal ions in salt lake brine to achieve the recovery of lithium ions. It not only has excellent selectivity and permeability, but also greatly reduces the cost compared with other separation membranes.
[0005] A method for preparing a composite membrane based on a covalent organic framework, the preparation method comprising the following steps:
[0006] Step 1: Weigh 4 mL of 1,4-dioxane and 2 mL of mesitylene according to the volume ratio and mix them to prepare 5 mL of mixed solution A;
[0007] Step 2: adding tetrakis(4-aminophenyl)methane:terephthalaldehyde in a molar ratio of 1:2 to the mixed solution A prepared in the first step and mixing evenly to prepare a mixed solution B;
[0008] Step 3: After ultrasonicating the mixed solution B for 0.2 to 0.5 h, 0.2 mL of 3M glacial acetic acid was added dropwise, and then ultrasonicated for another 0.2 to 0.5 h to obtain a mixed solution C;
[0009] Step 4: pretreating the polyacrylonitrile to obtain pretreated polyacrylonitrile;
[0010] Step 5: Add the pretreated polyacrylonitrile into the mixed solution C and put it into the reactor after it is completely immersed;
[0011] Step 6: Transfer the reactor to an oven for segmented heating reaction. After the heating reaction, a yellow film is formed on the surface of the polyacrylonitrile;
[0012] Step 7: Place the polyacrylonitrile with a yellow film formed on the surface in anhydrous ethanol, and after washing, obtain a composite membrane based on a covalent organic framework.
[0013] Furthermore, the ultrasonication in the third step is to ultrasonicate the mixed solution in an ultrasonic machine at room temperature for 0.2 to 0.5 h.
[0014] Furthermore, in the fourth step, the polyacrylonitrile is pretreated before being added to the solution C, and the pretreatment steps are:
[0015] Step 1: Soak polyacrylonitrile in dopamine hydrochloride solution and stir at a speed of 500 rpm. After running for 120 to 160 minutes, take out the PAN membrane, wash and dry it;
[0016] Step 2: Prepare 20 mL of 0.2 mmol APTES (3-aminopropyltriethoxysilane) solution, the solvent is isopropanol solution, and then pour the solution into a 50 mL three-necked flask, and then immerse the above-mentioned washed and dried polyacrylonitrile in the APTES (3-aminopropyltriethoxysilane) solution and heat it in an oil bath at 50-70°C for 6-8 hours, and nitrogen protection is performed during the heating process. After heating, take out the PAN membrane, wash and dry it;
[0017] Step 3: Pour 0.3 mmol of terephthalaldehyde into 20 mL of 1,4-dioxane to prepare a terephthalaldehyde solution, disperse it evenly and pour it into the inner tank of the reaction kettle. Soak polyacrylonitrile in the terephthalaldehyde solution and put it in an oven. The heating rate is 5°C / min to 150-170°C and heated for 1-2 hours. Then, take out the PAN film, wash and dry it to obtain the pretreated polyacrylonitrile.
[0018] Furthermore, in the fifth step, the diameter of the pretreated polyacrylonitrile is 1.5 cm, and the solution C is 5 mL.
[0019] Furthermore, in the sixth step, heating is performed in stages, with the heating temperature of the first stage being 50° C. and the heating time being 24 to 48 hours; and the heating temperature of the second stage being 70° C. and the heating time being 24 to 48 hours.
[0020] The present application also discloses a composite membrane based on a covalent organic framework, wherein the composite membrane based on a covalent organic framework consists of a COF membrane and a self-supporting flexible substrate; wherein the COF membrane is a covalent organic framework membrane, the covalent organic framework membrane is a 3D COF membrane with a pore size of 0.78 nm prepared by an interfacial polymerization method, and the component of the self-supporting flexible substrate is polyacrylonitrile PAN.
[0021] The present application also discloses the use of a composite membrane based on a covalent organic framework in the extraction of lithium from salt lake brine.
[0022] Principle explanation: The actual pore size of the 3D COF membrane is Between lithium ion water and diameter and magnesium ion water and diameter Through the principle of size screening, lithium ions can pass through, while magnesium ions are more difficult to pass through.
[0023] Beneficial effects:
[0024] 1. The transmission channel of the covalent organic framework has excellent separation performance for valuable metals due to the size effect. Compared with the separation membrane based on pore design, the covalent organic framework composite membrane provided by the present application has a more suitable pore size;
[0025] 2. Polyacrylonitrile has high mechanical strength and hydrophilicity, which increases the mechanical properties and flux of the composite membrane. Compared with other covalent organic frameworks, the pore size of the 3D COF in this application is more consistent with the size of hydrated lithium ions;
[0026] 3. The flexible substrate has high throughput. The composite membrane screens valuable metal ions through a covalent organic framework and effectively extracts lithium from salt lake brine;
[0027] 4. Compared with conventional commercial anion / cation exchange membranes, the covalent organic framework composite membrane provided by the present application has the separation performance of monovalent and divalent ions, and can be used to extract lithium from salt lake brine;
[0028] 5. The covalent organic framework composite membrane provided in the present application involves a polyacrylonitrile self-supporting substrate which is itself hydrophilic, so that the composite membrane has high selectivity and permeability;
[0029] 6. The preparation method of the covalent organic framework composite membrane provided in the present application has the advantages of simple and safe preparation process and is easy to achieve large-scale preparation.
[0030] 7. The covalent organic framework ion separation membrane (selective Li + / Mg 2 + =36), and polyacrylonitrile were used to prepare covalent organic framework composite membranes through interfacial polymerization. Compared with the existing commercial membranes (selective Li + / Mg 2+ =2), has high ion selectivity and permeability, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of the ion separation membrane of this application;
[0032] Figure 2 X-ray diffraction spectrum of the ion separation membrane of this application;
[0033] Figure 3 This is a graph showing the results of a permeation and diffusion test of a single solution under the test conditions of room temperature and normal pressure of the present application;
[0034] Figure 4 This is a graph showing the penetration and diffusion test results of the mixed solution of this application under the test conditions of room temperature and normal pressure. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0036] Unless otherwise specified, all numbers appearing in the specification and claims of this application, such as active components, temperature, time, pressure, etc., should not be understood as absolutely precise values. Due to the standard deviation of the measurement technology, the measured values inevitably have certain experimental errors.
[0037] Unless otherwise specified, the raw materials are tetrakis (4-aminophenyl) methane, terephthalaldehyde, glacial acetic acid, 1,4-dioxane, and mesitylene. The above raw materials are all commercial chemical agents with low cost. In addition, the preparation process of the method is simple and safe to operate, and it is easy to realize industrialization. The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0038] Example 1
[0039] A method for preparing a composite membrane based on a covalent organic framework, the preparation method comprising the following steps:
[0040] Step 1: Weigh 4 mL of 1,4-dioxane and 1 mL of mesitylene according to the volume ratio and mix them to prepare 5 mL of mixed solution A;
[0041] Step 2: adding tetrakis(4-aminophenyl)methane:terephthalaldehyde in a molar ratio of 1:2 to the mixed solution A prepared in the first step and mixing evenly to prepare a mixed solution B;
[0042] Step 3: After ultrasonicating the mixed solution B for 0.2 to 0.5 h, 0.2 mL of 3M glacial acetic acid was added dropwise, and then ultrasonicated for another 0.2 to 0.5 h to obtain a mixed solution C;
[0043] Step 4: pretreat polyacrylonitrile to obtain pretreated polyacrylonitrile. The pretreatment steps are as follows:
[0044] 1. Soak polyacrylonitrile in dopamine hydrochloride solution and stir at a speed of 500 rpm. After running for 120 to 160 minutes, take out the PAN membrane, wash and dry it;
[0045] 2. Prepare 20 mL of 0.2 mmol APTES (3-aminopropyltriethoxysilane) solution, the solvent is isopropanol solution, and then pour the solution into a 50 mL three-necked flask, and then immerse the above-mentioned washed and dried polyacrylonitrile in the APTES (3-aminopropyltriethoxysilane) solution and heat it in an oil bath at 50-70°C for 6-8 hours, and nitrogen protection is performed during the heating process. After heating, take out the PAN membrane, wash and dry it;
[0046] 3. Pour 0.3mmol of terephthalaldehyde into 20mL of 1,4-dioxane to prepare a terephthalaldehyde solution, disperse it evenly and pour it into the inner tank of the reaction kettle. Soak polyacrylonitrile in the terephthalaldehyde solution and put it into an oven. The heating rate is 5℃ / min to 150-170℃ and heated for 1-2h. Then take out the PAN film, wash and dry it to obtain the pretreated polyacrylonitrile.
[0047] Step 5: Add the pretreated polyacrylonitrile into solution C, the diameter of the polyacrylonitrile is 1.5 cm, and the solution C is 5 mL, and the mixture is completely immersed in the reactor;
[0048] Step 6: Transfer the reactor to an oven for segmented heating reaction. After the heating reaction, a yellow film is formed on the surface of the polyacrylonitrile. The heating temperature of the first segment is 50°C, and the heating time is 24 to 48 hours. The heating temperature of the second segment is 70°C, and the heating time is 24 to 48 hours.
[0049] Step 7: Place the polyacrylonitrile with a yellow film formed on the surface in anhydrous ethanol, and after washing, obtain a composite membrane based on a covalent organic framework.
[0050] The feed side ion solution used is chloride salt, and the concentration of the single ion solution is 0.1-0.5 mol / L; the mixed ion solution simulates the high magnesium-lithium ratio solution in the salt lake brine.
[0051] The covalent organic framework ion separation membrane described in this application is prepared by interfacial polymerization, and the covalent organic framework composite membrane is prepared by interfacial polymerization with polyacrylonitrile. Compared with the existing commercial membranes, it has higher ion selectivity and permeability, avoids expensive modification materials, and uses the most common and inexpensive polyacrylonitrile material as the substrate, so that the covalent organic framework composite membrane has excellent stability and mechanical properties, and has good application prospects in industrial applications.
[0052] Comparative Example 1
[0053] The polyacrylonitrile (PAN) membrane of this comparative example does not contain any covalent organic framework material component, specifically:
[0054] This comparative example is based on the same method as the example, except that the separation membrane does not contain a covalent organic framework, but only contains a polyacrylonitrile flexible substrate, and the membrane preparation process is the same as the example.
[0055] Figure 2 This is the X-ray diffraction spectrum of the ion separation membrane of the present application, indicating that the three-dimensional covalent framework material was successfully grown in situ on the commercial polyacrylonitrile membrane substrate by interfacial polymerization.
[0056] Figure 3 This is a graph showing the results of the permeation and diffusion test of a single solution under the test conditions of room temperature and normal pressure of the present application. The lithium ion selectivity and flux of Example 1 are significantly higher than those of Comparative Example 1.
[0057] Figure 4 This is a graph showing the results of the permeation and diffusion test of the mixed solution of the present application under the test conditions of room temperature and normal pressure. When simulating salt lake brine, Example 1 exhibits excellent lithium ion extraction performance.
[0058] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite membrane based on a covalent organic framework, characterized in that: The preparation method comprises the following steps: Step 1: Weigh 4 mL of 1,4-dioxane and 1 mL of mesitylene according to the volume ratio and mix them to prepare 5 mL of mixed solution A; Step 2: adding tetrakis(4-aminophenyl)methane:terephthalaldehyde in a molar ratio of 1:2 to the mixed solution A prepared in the first step and mixing evenly to prepare a mixed solution B; Step 3: After ultrasonicating the mixed solution B for 0.2 to 0.5 h, 0.2 mL of 3M glacial acetic acid was added dropwise, and then ultrasonicated for another 0.2 to 0.5 h to obtain a mixed solution C; Step 4: pretreating the polyacrylonitrile to obtain pretreated polyacrylonitrile. Step 5: Add the pretreated polyacrylonitrile into the mixed solution C and put it into the reactor after it is completely immersed; Step 6: Transfer the reactor to an oven for segmented heating reaction. After the heating reaction, a yellow film is formed on the surface of the polyacrylonitrile; Step 7: Place the polyacrylonitrile with a yellow film formed on the surface in anhydrous ethanol, and after washing, obtain a composite membrane based on a covalent organic framework.
2. The method for preparing a composite membrane based on a covalent organic framework according to claim 1, characterized in that: The ultrasonic treatment in the third step is to ultrasonicate the mixed solution in an ultrasonic machine at room temperature for 0.2 to 0.5 h.
3. The method for preparing a composite membrane based on a covalent organic framework according to claim 1, characterized in that: In the fourth step, polyacrylonitrile is pretreated, and the pretreatment steps are: Step 1: Soak polyacrylonitrile in dopamine hydrochloride solution and stir at a speed of 500 rpm. After running for 120 to 160 minutes, take out the PAN membrane, wash and dry it; Step 2: Prepare 20 mL of 0.2 mmol APTES (3-aminopropyltriethoxysilane) solution, the solvent is isopropanol solution, and then pour the solution into a 50 mL three-necked flask, and then immerse the above-mentioned washed and dried polyacrylonitrile in the APTES (3-aminopropyltriethoxysilane) solution and heat it in an oil bath at 50-70°C for 6-8 hours, and nitrogen protection is performed during the heating process. After heating, take out the PAN membrane, wash and dry it; Step 3: Pour 0.3 mmol of terephthalaldehyde into 20 mL of 1,4-dioxane to prepare a terephthalaldehyde solution, disperse it evenly and pour it into the inner tank of the reactor. Soak polyacrylonitrile in the terephthalaldehyde solution and put it in an oven. The heating rate is 5°C / min to 150-170°C and heated for 1-2 hours. Then, take out the PAN film, wash and dry it to obtain the pretreated polyacrylonitrile.
4. The method for preparing a composite membrane based on a covalent organic framework according to claim 1, characterized in that: In the fifth step, the diameter of the polyacrylonitrile is 1.5 cm, and the solution C is 5 mL.
5. The method for preparing a composite membrane based on a covalent organic framework according to claim 1, characterized in that: In the sixth step, heating is performed in stages, wherein the heating temperature of the first stage is 50° C., and the heating time is 24 to 48 hours; and the heating temperature of the second stage is 70° C., and the heating time is 24 to 48 hours.
6. A composite membrane based on a covalent organic framework prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The covalent organic framework-based composite membrane consists of a COF membrane and a self-supporting flexible substrate; wherein the COF membrane is a covalent organic framework membrane, the covalent organic framework membrane is a 3D COF membrane with a pore size of 0.78 nm prepared by an interfacial polymerization method, and the component of the self-supporting flexible substrate is polyacrylonitrile PAN.
7. Use of the covalent organic framework-based composite membrane according to claim 7 in the extraction of lithium from salt lake brine.
Citation Information
Cited By
Method for regulating and controlling functionalization of lithium battery diaphragm COFs based on catalyst concentration
CN120879142A